Pré-oxidação e adsorção em carvão ativado granular para remoção dos herbicidas Diuron e Hexazinona de água subterrânea - Dantas, Angela di Bernardo; Paschoalato, Cristina Filomena Pereira Rosa; Ballejo, Renata Rueda [UNESP]; di Bernardo, Luiz (FapUNIFESP (SciELO), 2009)
The cultivation of sugarcane demands the use of herbicides such as Diuron and Hexazinone. Some supply wells from Ribeirão Preto, SP, Brazil, built in the Guarani Aquifer are located in recharge points, and the presence of sandy Quartzarenic Neosol in these areas increases the vulnerability of the groundwater to contamination from herbicides This paper reports the water quality monitored in some wells located in the recharge area and the removal of Diuron and Hexazinone by means of adsorption in granular activated carbon (GAC), preceded or not by preoxidation with chlorine and chlorine dioxide in a pilot plant. The results indicated that Diuron was more strongly adsorbed than Hexazinone and that the saturation time of the GAC in the test with preoxidation was shorter than in the test without preoxidation, which may have occurred mainly due to the formation of by-products that competed with the adsorption of the herbicides.
Preoxidation and adsorption in granular activated carbon for the removal of Diuron and Hexazinone from groundwater
Keywords: Chlorine; Chlorine dioxide; Diuron; Granular activated carbon; Guarani aquifer; Herbicide; Hexazinone